GESTIÓN ADMINISTRATIVA EN EL DEPARTAMENTO DEL RECTORADO DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO - Goyes Muñoz, Ana Maria (2018)
Administrative management is vital for organizations' operations whether they are public or private, is focused primarily on administrative functions achieving institutional objectives efficiently and effectively for the shots of decisions with corrective actions. The main role of public institutions is the management of their personnel academic or administrative staff, teachers or students, in order to be a substantial part of the service activities of the citizens in the personal and social economic environment